The Influence of Permanganate Enhancement to Graphite on Chemical Structure and Properties of Graphene Oxide Material Generated by Improved Tour Method - Dyah Ayu Fatmawati; Triyono Triyono; Wega Trisunaryanti; Haryo Satriya Oktaviano; Uswatul Chasanah (Universitas Gadjah Mada, 2021)
Synthesis of graphene oxide (GO) material with variations in permanganate/graphite ratio has been carried out. This research purposes to study the impact of increasing oxidizing agents to graphite on the chemical structure and properties of the GO material produced. All GOs were synthesized using the improved Tour method with three variations of permanganate/graphite ratios of 5, 6, and 7. The results obtained include GO-5, GO-6, and GO-7, respectively, having a d spacing value of 0.843; 0.891; 0.894 nm by XRD analysis and 0.768; 0.756; 0.772 nm by SAED analysis. Based on the FTIR data, all GO materials bring up the peaks of oxygen-functionalized carbon absorption such as O–H, C–H sp3, C=O, C–O–C of ether and ester, and C-OH for carboxylic acids and alcohols. The oxidation levels (O/C ratio taken from EDX data) of GO-5, GO-6, and GO-7 are 0.67, 0.88, and 1.50, respectively. SEM images display the appearance of an exfoliated layer with a wrinkled and irregular surface. TEM images show thin and transparent layers. The main peaks with the highest absorbance at the wavelength around 230-240 nm, meanwhile the band gap energy produced was 3.53; 3.71; 3.55 eV for GO-5, GO-6, and GO-7, respectively.